Transcription Factor Families Have Much Higher Expansion Rates in Plants than in Animals - Shiu, S.-H.; Shih, M.C.; Li, W.H.
Transcription factors (TFs), which are central to the regulation of gene expression, are usually members of multigene families. In plants, they are involved in diverse processes such as developmental control and elicitation of defense and stress responses. To investigate if differences exist in the expansion patterns of TF gene families between plants and other eukaryotes, we first used Arabidopsis (Arabidopsis thaliana)TFs to identify TF DNA-binding domains. These DNA-binding domains were then used to identify related sequences in 25 other eukaryotic genomes. Interestingly, among 19 families that are shared between animals and plants, more than 14 are larger in plants than in animals. After examining the lineage-specific expansion of TF families in two plants, eight animals, and two fungi, we found that TF families shared among these organisms have undergone much more dramatic expansion in plants than in other eukaryotes. Moreover, this elevated expansion rate of plant TF is not simply due to higher duplication rates of plant genomes but also to a higher degree of expansion compared to other plant genes. Further, in many Arabidopsis-rice (Oryza sativa)TF orthologous groups, the degree of lineage-specific expansion in Arabidopsis is correlated with that in rice. This pattern of parallel expansion is much more pronounced than the wholegenome trend in rice and Arabidopsis. The high rate of expansion among plant TF genes and their propensity for parallel expansion suggest frequent adaptive responses to selection pressure common among higher plants.